Land Acquisition in the Context of Yogyakarta's Special Region: Policy Implementation in the Development of the Yogyakarta-Bawen Toll Road - Kurniawan, Boby; Said, Abdullah; Hanafi, Imam (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
This study aims to examine the implementation of land acquisition policy for the construction of the Yogyakarta–Bawen Toll Road in the Special Region of Yogyakarta (DIY), with particular attention to the challenges arising from the region's special autonomous status. The main focus is on the application of Law No. 2 of 2012, which must take into account the distinctive land tenure structure in DIY, especially the existence of Sultan Ground. This research adopts a qualitative descriptive approach and is conducted in Kalurahan Tirtoadi, Kapanewon Mlati, Sleman. The conceptual framework views policy implementation through three key dimensions: process, output, and outcome. The findings reveal that although the output namely land provision was nearly achieved through compensation schemes and the granting of pisungsung for the use of Sultan Ground, the implementation process remains suboptimal. Key obstacles include issues related to inherited land and the limited mechanisms for replacing endowed (waqf) land. Furthermore, the policy outcomes show multi-dimensional impacts, including economic, psychological, and environmental effects.